Not for Alms but Help: Fund-raising and Free Education for the Blind - Pearce, Joanna (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2012)
When the Halifax Asylum for the Blind opened its doors to students in 1872, its funding came from charitable donations, with only limited financial support from the provincial government. However, sighted children in Nova Scotia had been entitled to tax-based funding for their education since the 1864 Free Schools Act. To ensure sufficient funding for his students, Charles Frederick Fraser, the blind Superintendent of the Asylum, began an appeal to bring in additional donations. Fraser then used the same appeal to persuade the Nova Scotian government to provide tax-based funding in a similar manner to that available for educating sighted students, arguing that his students were citizens just as much as their sighted counterparts. Fraser contended that funding the education of blind children was a sound fiscal move on the part of the provincial and municipal governments as it would eliminate the far greater expense of caring for unemployable, despondent blind adults. This paper explores the importance of Fraser’s campaign in the fight for rights for blind people in the Maritime provinces.